TRPA1 Activation-Induced Myelin Degradation Plays a Key Role in Motor Dysfunction After Intracerebral Hemorrhage - Xia, Min; Chen, Weixiang; Wang, Jie; Yin, Yi; Guo, Chao; Li, Chengcheng; Li, Mingxi; Tang, Xiaoqin; Jia, Zhengcai; Hu, Rong; Liu, Xin; Feng, Hua (Frontiers in Molecular Neuroscience, 2019)
Intracerebral haemorrhage (ICH) is a devastating disease that is characterized by high morbidity and high mortality. ICH has an annual incidence of 10–30/100 000 people and accounts for approximately 10% to 30% of all types of stroke. ICH mostly occurs at the basal ganglia, which is rich in nerve fibres; thus, hemiplegia is quite common in ICH patients with partial sensory disturbance and ectopic blindness. In the clinic, those symptoms are considered to originate from the white matter injury in the area, but the exact mechanisms are unknown, and currently, no effective drug treatments are available to improve the prognosis. Clarifying the mechanisms will contribute to the development of new treatment methods for patients. The transient receptor potential ankyrin 1 (TRPA1) channel is a non-selective cation channel that play a role in inflammatory pain sensation and nociception, and may be a potential regulator in emotion, cognition and social behaviour. Here, we report that TRPA1 is involved in myelin damage and oxidative stress injury in a mouse ICH model. Intervention with the TRPA1 channel may be a new method to improve the motor function of patients in the early stage of ICH.